2013
DOI: 10.1097/wnf.0b013e3182996400
|View full text |Cite
|
Sign up to set email alerts
|

Duloxetine Is Effective in Treating Depression in Multiple Sclerosis Patients

Abstract: The results suggest that duloxetine is well tolerated, safe, and effective in reducing depression and fatigue in MS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Moreover, animal models have provided increasing evidence of the possible neuroprotective and neurodegenerative actions of fluoxetine [28]. Duloxetine was the second most prescribed antidepressants observed in our study, which is not unexpected because an open-label study demonstrated its safety, tolerance, and efficacy in reducing depression among individuals with MS [29]. Existing studies have also demonstrated the benefits of using other commonly prescribed antidepressants such as escitalopram [30], sertraline [31], and paroxetine [32] which were observed in our study to a lesser degree.…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, animal models have provided increasing evidence of the possible neuroprotective and neurodegenerative actions of fluoxetine [28]. Duloxetine was the second most prescribed antidepressants observed in our study, which is not unexpected because an open-label study demonstrated its safety, tolerance, and efficacy in reducing depression among individuals with MS [29]. Existing studies have also demonstrated the benefits of using other commonly prescribed antidepressants such as escitalopram [30], sertraline [31], and paroxetine [32] which were observed in our study to a lesser degree.…”
Section: Discussionmentioning
confidence: 68%
“…Treatment of MS patients with duloxetine, a SNRI (Solaro et al . ), reduced depression and fatigure; however, neurological symptoms were not evaluated. It has also been reported that treatment with phosphodiesterase inhibitors, which prevent breakdown of cAMP, provides benefit (Suzumura et al .…”
Section: Reducing Na Loss and Lc Damage In Human Diseasesmentioning
confidence: 99%
“…Treatment with a mixture of lofepramine (a NARI that is metabolized to desipramine) and phenyalanine (a precursor of tyrosine) relieved symptoms of MS (Loder et al 2002;Wade et al 2002) as well as reduced lesion volume (Puri et al 2001) in a relatively large cohort (n = 69 drug-treated and n = 69 placebo-treated) of patients. Treatment of MS patients with duloxetine, a SNRI (Solaro et al 2013), reduced depression and fatigure; however, neurological symptoms were not evaluated. It has also been reported that treatment with phosphodiesterase inhibitors, which prevent breakdown of cAMP, provides benefit (Suzumura et al 2000), although it is likely that cAMP levels are due not only to NA activation of bARs but to other activators of adenylate cyclase activity.…”
Section: Vindeburnolmentioning
confidence: 99%
“…Some reports studied the use of antidepressant drugs in MS 710 , all of which indicated their beneficial effects regarding depression related symptoms. Indeed, very few studies investigated the potential immunosuppressive effect of fluoxetine 11 and sertraline 12 in animal models of MS. On the other hand, only one study in MS patients with major depression showed the efficacy of fluvoxamine 8 .…”
Section: Introductionmentioning
confidence: 99%